PENGARUH GAYA KEPEMIMPINAN, MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA CV. GENTA JAYA STEEL - Rini; Rifai, Nurdin (Jurnal Gici Jurnal Keuangan dan Bisnis, 2024)
The purpose of this study is to determine and analyze the influence of leadership style, motivation and work discipline on employee performance on CV. Genta Jaya Steel in Bogor. The data analysis model used is multiple linear regression analysis. Sample selection is done by means of nonprobability sampling. The sample amounted to 102 respondents, using multiple linear analysis. The results of the regression test show that 42% of employee performance factors can be explained by leadership style, motivation and work discipline, while the remaining 68% is explained by other factors not examined in this research. Meanwhile, the results of the F test show that simultaneously the variables leadership style, motivation and work discipline simultaneously have a positive and significant effect on employee performance with the analysis results being the value Fcount (25,141) > Ftable (2,460). The results of the t test show that the Leadership Style variable shows the results of tcount (3.650), the Motivation variable shows the results of tcount analysis (3.852), the work discipline variable shows the results of tcount analysis (3.094), where ttable (1.98350), then partially these three variables have an effect positive and significant on employee performance at CV. Genta Jaya Steel. The dominant variable influencing employee performance is motivation.